2007
DOI: 10.1158/1078-0432.ccr-06-1551
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypes, Loss of Heterozygosity, and Expression Levels of Glycine N-Methyltransferase in Prostate Cancer

Abstract: Purpose: Glycine N-methyltransferase (GNMT) affects genetic stability by regulating DNA methylation and interacting with environmental carcinogens. In a previous study, we showed that GNMT acts as a susceptibility gene for hepatocellular carcinoma. Here, we report on our efforts to characterize the haplotypes, loss of heterozygosity (LOH), and expression levels of the GNMT in prostate cancer. Experimental Design: Peripheral blood mononuclear cell DNA collected from 326 prostate cancer patients and 327 age-matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
59
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 28 publications
4
59
3
3
Order By: Relevance
“…18 This group has reported that GNMT expression is localized in the cytoplasm of hepatocytes 19 and in both the cytoplasm and nucleus of prostate epithelium. 12 Their findings are consistent with our immunohistochemical data, indicating that GNMT expression is predominantly located in the cytoplasm and scattered in the nuclei of prostate cells.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…18 This group has reported that GNMT expression is localized in the cytoplasm of hepatocytes 19 and in both the cytoplasm and nucleus of prostate epithelium. 12 Their findings are consistent with our immunohistochemical data, indicating that GNMT expression is predominantly located in the cytoplasm and scattered in the nuclei of prostate cells.…”
Section: Discussionsupporting
confidence: 92%
“…GNMT may have an important role in promoting prostate cancer cell growth via the regulation of apoptosis. Our results seem to disagree with previous findings that GNMT is a tumor susceptibility gene, [10][11][12] but agree with the previous findings that GNMT activity is linked with the progression of cancer. 5 According to our findings, we hypothesize that GNMT expression may correlate with malignant progression and prognosis.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations